Inflammatory gene expression in adipose tissue according to diagnosis of anxiety and mood disorders in obese and non-obese subjects. Issue 1 (December 2018) - Coín-Aragüez, Leticia; Pavón, Francisco; Contreras, Alba; Gentile, Adriana-Mariel; Lhamyani, Said; De Diego-Otero, Yolanda; Casado, Yolanda; Oliva Olivera, Wilfredo; Olveira, Gabriel; Tinahones, Francisco; Pérez Costillas, Lucía; El Bekay, Rajaa
Abstract Psychiatric disorders have been widely reported to be associated with systemic inflammation upregulation and adiposity. However, there are no data that link adipose tissue inflammation to these mental disorders. The analysis of adipokines and inflammation-related markers in adipose tissue could help to elucidate the potential association between obesity and mental health. An observational study was conducted in samples of patients consisting of non-obese and obese subjects, who were diagnosed with anxiety or mood disorders. Gene expression of adiponectin (ADIPOQ ), leptin (LEP ) and inflammatory markers (IL6, IL1B, TNF, CCL2, CSF3, ITGAM, andPLAUR ) were determined in visceral (VAT) and subcutaneous (SAT) adipose tissues. Our results showed that the gene expression of adipokines and inflammation-related markers was higher in the VAT and SAT of obese subjects compared with non-obese subjects. Regarding mental disorders, all the inflammatory genes in the VAT were significantly higher in non-obese subjects with anxiety or mood disorders than in subjects without mental disorders, except forTNF andITGAM . Additionally, IL6 expression was significantly lower in SAT. In contrast, obese patients diagnosed with anxiety or mood disorders only showed significantly lower expression levels ofIL1B in VAT andADIPOQ in SAT when compared with obese subjects without mental disorders. These data suggest the potential involvement of VAT inflammation in anxiety and mood disorders, involving complex mechanisms which are strongly affected by obesity.